Factors affecting seed production in Pseudotsuga macrolepis flous in the state of Hidalgo, Mexico - Zavala Chavez, Fernando; Mendez Montiel, Jose Tulio (Instituto de Ecología, A.C., 1996)
The purpose of this work was to investigate the effect of pollination and insects incidence in both quality and quantity of seeds of Pseudotsuga macrolepis available for its natural regeneration in the Western portion of Sierra de Pachuca, state of Hidalgo. Pollination and insects incidence were controlled experimentally. Results appear to indicate that some seeds were developed through parthenogenesis. In addition, ineffective pollination and attack of insects can decrease the amount of potential and produced seeds. Because there are practically no seeds for natural regeneration, we conclude that an artificial repopulation of P. macrolepis is necessary.